Cost Plus Net Value Change (C+NVC) Revisited: A Sequential Formulation of the Wildfire Economics Model. Issue 2 (5th November 2018) - Rossi, David; Kuusela, Olli-Pekka
Abstract: The effectiveness of annual investments in US wildfire management programs has been subject to public criticism. One source of inefficiency may arise from a fragmented budgeting process. In the United States, federal budgets for wildfire management operations are not determined simultaneously by a single decision rule but instead independently by separate criteria. This paper investigates the conditions under which fragmented budgeting will constrain the fire management organization from the attainment of a socially optimal allocation. To accomplish this, we extend the standard model of wildfire economics to account for a sequential decision process inherent to a fragmented budgeting procedure. It is shown that when incident commanders weight the dual objectives of mitigating fire damage and suppression costs evenly, a fragmented budgeting structure does not constrain the fire management organization from reaching a socially optimal allocation. However, with the availability of supplementary suppression funds and the added public pressure to limit wildfire damage, incident commanders may weigh the goal of damage mitigation more heavily than the goal of lowering costs when requesting suppression resources. In this case, incident commanders fail to internalize the full costs of suppression and this creates a circumstance where fragmented budgeting leads to program inefficiency.